2004
DOI: 10.1042/bj20030638
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interaction between piD261/Bud32, an evolutionarily conserved protein kinase of Saccharomyces cerevisiae, and the Grx4 glutaredoxin

Abstract: The Saccharomyces cerevisiae piD261/Bud32 protein and its structural homologues, which are present along the Archaea-Eukarya lineage, constitute a novel protein kinase family (the piD261 family) distantly related in sequence to the eukaryotic protein kinase superfamily. It has been demonstrated that the yeast protein displays Ser/Thr phosphotransferase activity in vitro and contains all the invariant residues of the family. This novel protein kinase appears to play an important cellular role as deletion in yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 45 publications
8
75
1
Order By: Relevance
“…3 and 4). In support of this hypothesis, recent studies indicate that monothiol Grxs can modulate cellular signaling events through protein-protein interactions mediated by PICOT-HD (23,26,51). Future work will be necessary to determine the target(s) of AtGRXcp and understand the complexity of ROS regulation in planta.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…3 and 4). In support of this hypothesis, recent studies indicate that monothiol Grxs can modulate cellular signaling events through protein-protein interactions mediated by PICOT-HD (23,26,51). Future work will be necessary to determine the target(s) of AtGRXcp and understand the complexity of ROS regulation in planta.…”
Section: Discussionmentioning
confidence: 89%
“…Yeast Grx5 encodes a mitochondrial monothiol Grx, which is required for biogenesis of iron-sulfur clusters, whereas Grx3 and Grx4 function in detoxification of cytotoxin and cell proliferation in yeast (21)(22)(23). Interestingly, bacterial Grx4, unlike other previously characterized Grxs, can serve as a substrate for thioredoxin reductase instead of NADPH/glutathione reductase (20), suggesting that those monothiol Grxs have distinct functions.…”
mentioning
confidence: 99%
“…These five Grxs also differ in regard to their subcellular localization. Grx1 is cytosolic, Grx3 and Grx4 are nuclear (17,23), Grx5 is mitochondrial (24), and Grx2 has a dual localization in the cytosol and mitochondria (16). Grx2 stands out among other Grxs for its efficiency in transferring reducing equivalents from reduced lipoamide to oxidized glutathione (25).…”
mentioning
confidence: 99%
“…A yeast two-hybrid assay has shown that Bud32 interacts with IMD (Inosine Monophosphate Dehydrogenase) proteins; thus, Drosophila Prpk might participate in guanosine synthesis (Lopreiato et al, 2004). Guanosine deficiency could explain the reduction in larval growth (guanosine auxotroph); however, da>Prpk-IR larvae grown in media supplemented with 2 mg/ml of guanosine, a treatment previously used to overcome guanosine deficiency in Drosophila (O'Donnell et al, 2000), did not recover the growth phenotype (Fig.…”
Section: Drosophila Prpkmentioning
confidence: 99%
“…Importantly, the growth phenotype in larval tissue is cellautonomous, ruling out indirect effects due to alterations in the larval nutrient sensor mechanism (Colombani et al, 2003). This phenotype could be explained using data from a yeast two-hybrid assay, which shows that Bud32 interacts with IMD proteins and with glutaredoxin (Grx4) (Lopreiato et al, 2004), which suggests a role for Bud32 in nucleoside biosynthesis and REDOX balance. However, Prpk-depleted larvae fed with guanosine did not recover their normal size and no obvious REDOX variations were detected using the dihydro-dichloro-fluorescein di-acetate probe in Prpkdepleted clones (data not shown), arguing against either possibility.…”
Section: Prpk Is Required To Sustain Organ Growth To Attain Final Bodmentioning
confidence: 99%